STUDY OF THE TEMPERATURE CONDITION OF SURFACE WATERS OF NOVOTROITSKY RESERVOIR BASED ON REMOTE SENSING DATA AND EVALUATION OF ITS IMPACT ON FISH GROWTH AND DEVELOPMENT - Evgeniy G. Mishvelov; Ivan A. Bakumenko; Anatoliy F. Shevkhuzhev; Vladimir A. Pogodaev (Юг России: экология, развитие)
Aim. The aim of the study is to analyze and reveal the features of the temperature regime of the Novotroitsky water reservoir surface based on remote sensing data; to determine the influence of the temperature regime of the surface waters of Novotroitsky reservoir on the ecological state of the reservoir, as well as to determine the areas of the surface water zones of the Novotroitsky reservoir with optimal and unfavorable temperature conditions for fish. Methods. The temperature values of the earth's surface (water area) were calculated according to the generally accepted methodology. Its essence lies in the fact that the calculation of the earth's surface temperature is performed after radiometric calibration of the images and compensation of the effect of the optical density of the atmosphere taking into account the emissivity of various objects on the earth's surface. The calculations were performed separately for the 10 and 11 channels of images from the Landsat 8 satellite, and then averaged. Results. Were established the quantitative characteristics of the inhomogeneity of the temperature fields of the water surface of Novotroitsky reservoir during the summer period due to discharges of the heated waters of the Stavropol GRES power plant. The peculiarities of the spatial variability of the temperature fields of the Novotroitsky water reservoir surface in summer season were revealed. It is shown that the use of the Novotroitsky water reservoir as a reservoir-cooler is potentially accompanied by the development of eutrophication processes and creation of risks for drinking purposes, as well as cultural, household and fishery use. The table shows the data demonstrating the temperature condition of the Novotroitsky reservoir water surface. The figure shows the temperature fields of the surface of the Novotroitsky water reservoir. Conclusions. In summer period, half of the water area of the Novotroitsky water reservoir can be attributed to the zones of optimum temperatures for the juvenile pikeperch. Were revealed the periods when the reservoir becomes practically unsuitable for growth and development of juveniles of oxyphilic fish. Excessive rise of water temperature in summer was established in accordance with SanPiN (Sanitary Rules and Regulations) 2.1.5.980-00.2.1.5. Such an increase in temperature is observed in 13-16% of the whole water area.